Technology for early childhood education and socialization : developmental applications and methodologies - Blake, Sally, 1949-; Izumi-Taylor, Satomi, 1948- (Hershey, PA : Information Science Reference, 2010)
'This book provides readers with valuable and authentic research on how technology relates to early childhood growth'--Provided by publisher
Includes bibliographical references and index
Keywords: Early childhood education -- Computer-assisted instruction; Education -- Effect of technological innovations on; Children -- Effect of technological innovations on; Child development; Social learning